A Sectoral Analysis of PSAK 73’s Impact on Financial Reporting and Covenant Compliance: Implications for State-Owned Enterprises on Indonesia’s Strategic Projects - Bagus Satrio Utomo,; Herry Respati Kusuma,; Novita Triyatun,; Ince Ahmad Zarqan, (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
Implementation of PSAK 73 (Leases, now superseded by PSAK 116), Indonesia's adoption of IFRS 16, represents a structural shift in financial reporting, affecting ratio volatility and decision-making for public entities, particularly State-Owned Enterprises (BUMN) executing National Strategic Projects (PSN). By eliminating the operating lease classification, the standard mandates Right-of-Use (RoU) asset and lease liability recognition for virtually all contracts, effectively ending off-balance-sheet financing. Comparison from PT Garuda Indonesia Tbk, PT Telkom Indonesia Tbk, PT Jasa Marga Tbk, and construction SOEs (BUMN Karya) demonstrates sector-dependent effects. While aviation liabilities surged over 8,600% and telecommunications rose 548.5%, the construction and energy sectors faced unique challenges related to heavy equipment and infrastructure leases. The standard distorts key financial metrics, artificially inflating EBITDA and Operating Cash Flow (OCF), while depressing Return on Assets (ROA) and exacerbating Debt-to-Equity Ratios (DER). These distortions create significant risks of "technical default" on debt covenants and compromise the accuracy of capital budgeting models (NPV/IRR) used for strategic project evaluation. The analysis further examines secondary effects, including agency theory implications on managerial behavior, the rise of short-term lease engineering, and the divergence between credit rating methodologies and banking covenant compliance. PSAK 73 enhances transparency but necessitates a fundamental recalibration of financial analysis frameworks, funding strategies, and asset management practices.